Evaluation of Injuries in Patients with Blunt Abdominal Trauma by Ultrasonography taking Computerized Tomography as Gold Standard Imaging Modality-Experience at Liaquat National Hospital - Mohsin, Nadia; Jesrani, Ameet; Mahmud, Roomi; Nizamani, Waseem Mehmood; Ali, Mubarak (Journal of Liaquat University of Medical & Health Sciences, 2019)
BACKGROUND: Consequent upon blunt abdominal trauma liver, spleen and kidneys are most vulnerable organs to be affected. Rapid diagnosis and appropriate management are key factors to reduce the risk of preventable death. More than 25 years ago Ultrasonography (US) was described for evaluation of injuries in blunt abdominal trauma and presently is being used as the primary imaging modality. OBJECTIVE: To determine the diagnostic accuracy of Ultrasonography in evaluation of injuries in patients with blunt abdominal trauma by comparing findings with computed tomography taken as the gold standard imaging modality. METHODOLOGY: Total 100 patients of blunt abdominal trauma having clinical suspicion of intra-abdominal injury such as abdominal pain, tenderness, hematuria and decreasing hemoglobin level were studied. Ultrasound using a convex probe with frequency of 3.75 MHz was performed. Images were taken in serial transverse and longitudinal planes. Computed tomography after oral and intravenous contrast administration was also performed in all cases. Sensitivity, specificity, PPV, NPV, and accuracy of Ultrasonography were calculated using Computerized Tomography as gold standard imaging modality. RESULTS: The mean age of study population was 33.9 ±12.8 years. There were 52 (52%) males and 48 (48%) females. Sensitivity of ultrasound for evaluation of injuries in these traumatic patients was 91.9%, specificity was 84.6%, positive predictive value was 94.4%, negative predictive value was 78.6% and accuracy was 90% in the evaluation of injuries in blunt abdominal trauma. CONCLUSION: Ultrasonography is an effective, safe and easily available imaging modality with high diagnostic value for evaluation of patients with injuries due to blunt abdominal trauma, and therefore may be used as the primary imaging modality in blunt abdominal trauma.